1993
DOI: 10.1246/bcsj.66.814
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effect on the Enthalpies of Formation of CH/π Complexes of Aromatic π-Bases

Abstract: The formation constants and the enthalpies of formation of CH/π complexes were determined for a series of ternary chloroform/aromatic π-base/carbon tetrachloride (solvent) systems. The enthalpies showed that the interaction is favored by the electron-releasing substituent on the aromatic ring. Electronegative substituents on the CH donor also strengthen the interaction. The fact renders a support on the hydrogen-bond-like nature of the CH/π interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 16 publications
1
32
0
Order By: Relevance
“…We determined the stabilization energies of chloroform-arene complexes, and showed that the interaction becomes stronger when the arene becomes more electron-rich. 6 On the other hand, the stabilization energy of hydrogen bonds was shown to be attributable to the combined contributions of coulombic, delocalization, dispersion and exchange repulsion terms between hydrogen (XH) and other nonbonded electronegative atoms. 7,8ab Quantum mechanical calculations indicated the contribution of similar energy terms to OH-p and CH-p interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We determined the stabilization energies of chloroform-arene complexes, and showed that the interaction becomes stronger when the arene becomes more electron-rich. 6 On the other hand, the stabilization energy of hydrogen bonds was shown to be attributable to the combined contributions of coulombic, delocalization, dispersion and exchange repulsion terms between hydrogen (XH) and other nonbonded electronegative atoms. 7,8ab Quantum mechanical calculations indicated the contribution of similar energy terms to OH-p and CH-p interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Hammett (log K rel vs s) plots on the NOE enhancements of intramolecularly CH±p interacted systems in dimethyl-d6 sulfoxide a As f HAr (H donor ) is proportional to the amount of CH-p interacted folded conformer, log[f HAr (H donor )] was used as a substitute for log K rel .…”
mentioning
confidence: 99%
“…properties [25]. Support for the nature of the hydrogen bond has been provided by the monitoring of electronic substituent effects upon spectroscopic data [26], conformational equilibrium [27], enantiomeric selection [28], selectivity in organic reactions [29], and coordination chemistry [30].…”
Section: Evidence and The Nature Of The Ch/π Hydrogen Bondmentioning
confidence: 99%
“…25 shows the original search method probing the CSD. The data for the intermolecular interaction in organic crystals are listed in…”
mentioning
confidence: 99%
“…[5] A similar conclusion was drawn by Umezawa et al [6] Theoretical calculations revealed that the origin of the interaction is mainly a dispersion energy. [7] Thus, a single CH···π interaction is very weak (4-14 kJ mol -1 ), [8] but the total energy can be much more significant as a result of the simultaneous operation of many such interactions.…”
Section: Introductionmentioning
confidence: 99%